(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Badland formations are an ever-expanding network of erosive channels that make landunsuitable for cultivation and other uses. The Narmada Sherrivers’ alluvium badland trail is situated inIndia’s central region. Using top sheets from the Survey of India (SOI), the area’s base map is divided intobadland and other land. For morphological characterization, two separate primary badlands have beenfound. The several map layers for drainage system, contours elevations, distance mapping, isopach(depth of alluvium deposits), slope are acquired in a GIS environment.According to the study’sfindings, more than 75 of the badland area’s alluvium deposits have been developed. The soft alluviumdeposit is a primary reason for the badland’s spread onto the alluvium geological area since it is moresusceptible to gull erosion. After developing MIE, applying it to the study area, verifying its accuracywith field data, we may now assess the degree to which badland watersheds are eroded.